Effect of Tai Chi on Cognitive Function among Older Adults with Cognitive Impairment: A Systematic Review and Meta-Analysis. (5th August 2021) - Gu, Renjun; Gao, Yujia; Zhang, Chunbing; Liu, Xiaojuan; Sun, Zhiguang
Abstract : Background . Cognitive decline occurs in all persons during the aging process and drugs can only alleviate symptoms and are expensive. Some researches demonstrated that Tai Chi had potential in preventing cognitive decline while others' results showed Tai Chi had no influence on cognitive impairment. Therefore, we conduct a systematic review and meta-analysis to assess the efficacy and safety of cognitive impairment patients practicing Tai Chi. Methods . A comprehensive literature search was carried out in multiple databases, including PubMed, Cochrane, MEDLINE (Ovid), Web of Science, Embase, Scopus, PsycInfo (Ovid), CKNI, Wan Fang, VIP, SinoMed, and ClinicalTrails, from their inception to 1 July 2020 to collect randomized controlled trials about practicing Tai Chi for patients with cognitive impairment. Primary outcomes included changes of cognitive function and secondary outcomes included changes of memory functions. Data were extracted by two independent individuals and Cochrane Risk of Bias tool version 2.0 was applied for the included studies. Systematic review and meta-analysis were performed by RevMan 5.3 software. Results . The results included 827 cases in 9 studies, of which 375 were in the experimental group and 452 were in the control group. Meta-analysis showed that Mini-Mental State Examination WMD = 1.52, 95% CI [0.90, 2.14]; Montreal Cognitive Assessment WMD = 3.5, 95% CI [0.76, 6.24]; Clinical Dementia Rating WMD = −0.55, 95% CI [−0.80, −0.29]; logical memory delayed recall WMD = 1.1, 95% CI [0.04, 2.16]; digit span forward WMD = 0.53, 95% CI [−0.65, 1.71]; and digit span backward WMD = −0.1, 95% CI [−0.38, 0.19]. No adverse events were reported in the included articles. Conclusion . There is limited evidence to support that practicing Tai Chi is effective for older adults with cognitive impairment. Tai Chi seems to be a safe exercise, which can bring better changes in cognitive function score.